Do heterogeneous expectations constitute a challenge for policy interaction? - Emanuel Gasteiger (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
Yes, indeed; at least for macroeconomic policy interaction. We examine a Neo-Classical economy and provide the conditions for policy arrangements to successfully stabilize the economy when agents have either rational or adaptive expectations. For a contemporaneous-data monetary policy rule, the monetarist solution is unique and stationary under a passive fiscal/active monetary policy regime if monetary policy appropriately incorporates expectational heterogeneity. In contrast, the active fiscal/passive monetary policy regime's fiscalist solution is prone to explosiveness due to empirically plausible expectational heterogeneity. Nevertheless, this can be a well-defined, rather orthodox equilibrium. For operational monetary policy rules, only the results for the fiscalist solution prevail. Moreover, our results are plausible from an adaptive learning viewpoint.
Keywords: E31; D84; E52; E62; 330; inflation; heterogeneous expectations; fiscal and monetary policy interaction